Intersex interventions as human rights violations: The European Court of Human Rights sets out guiding principles in M v France - Alaattinoğlu Daniela (Wiley-Blackwell, 2025)
In 2022, the European Court of Human Rights, for the first time, signalled that it regards non-consensual interventions on intersex individuals which are not motivated by medical necessity as human rights violations. This case note argues that the admissibility decision in question, M v France, albeit ruled inadmissible on procedural grounds, constitutes an important step towards binding supranational human rights standards, particularly regarding torture and ill-treatment. While M v France could inspire intersex people to further their claims as strategic litigation, the note reflects on the central questions invoked by the Court's decision and some of the legal hurdles that intersex people may face when approaching courts with claims for recognition and redress.